Manajemen strategi dalam penguatan kepercayaan nasabah terhadap lembaga keuangan syariah - Muawanah, Nurul (Maliki Interdisciplinary Journal, 2025)
Customer trust is the main foundation for the sustainability of Islamic financial institutions. In the increasingly competitive financial industry, the implementation of strategic management is a key factor in building, maintaining, and strengthening customer trust in Islamic-based financial institutions. This study aims to analyze the role of strategic management in strengthening customer trust in Islamic financial institutions in Indonesia. Amid the increasing competition between conventional and Islamic financial entities, trust serves as the key determinant of customer loyalty and long-term institutional sustainability. This research is based on a literature review of ten academic journals covering aspects such as the application of sharia principles, Islamic financial literacy, marketing strategies, Good Corporate Governance (GCG), and public education on Islamic banking products. The findings indicate that customer trust can be enhanced through consistent implementation of sharia principles, improvement of service quality, adoption of Islamic value-based marketing strategies, institutional transparency and accountability, and continuous public education. The integration of these strategic elements forms the essential foundation for Islamic financial institutions to strengthen credibility, reputation, and competitiveness within the national financial industry.